Characteristics of SARS-CoV-2 Omicron BA.5 variants in Shanghai after ending the zero-COVID policy in December 2022: a clinical and genomic analysis - Liu, Pengcheng; Cai, Jiehao; Tian, He; Li, Jingjing; Lu, Lijuan; Xu, Menghua; Zhu, Xunhua; Fu, Xiaomin; Wang, Xiangshi; Zhong, Huaqing; Jia, Ran; Ge, Yanling; et al. (Frontiers in Microbiology, 2024)
An unprecedented surge of Omicron infections appeared nationwide in China in December 2022 after the adjustment of the COVID-19 response policy. In this study, we report the clinical and genomic characteristics of SARS-CoV-2 Omicron BA.5 infections among children in Shanghai during the outbreak in late December 2022. We sequenced 64 SARS-CoV-2 positive samples obtained from hospitalized children. The genomic monitoring revealed that the emerging BA.5.2.48 and BF.7.14 were the dominant subvariants. Additionally, the BA5.2.48 infections were more frequently observed to experience vomiting/diarrhea and less frequently present cough compared to the BF.7.14 infections among patients without comorbidities in the study. The highfrequency unique non-synonymous mutations were present in BA.5.2.48 (N: Q241K) and BF.7.14 (nsp2: V94L, nsp12: L247F, S: C1243F, ORF7a: H47Y) with respect to their parental lineages. Of these mutations, C1243F mutation in S protein, L247F mutation in nsp12, and H47Y mutation in ORF7a protein were predicted to have a deleterious effect on the protein function. Besides, the H47Y mutation was also found to increase the stability of the ORF7a protein. Further in vitro to in vivo studies are needed to verify the role of these specific mutations in viral fitness. In addition, continuous genomic monitoring and clinical manifestation assessments of the emerging variants will still be crucial for the effective responses to the ongoing COVID-19 pandemic.